Stereotactic and its association with cognitive performance career: صلاح نوري محمود - ظبية محمد (Al-Academy, 2016)
The importance of this study of the growing importance of perception of touch and its association with the job performance of industrial product since the perception stereotactic means he means practiced by the individual through job performance and has assets of knowledge in the mind of the user and require him to mind the capabilities and knowledge cognitive following their individual focus Zhennea.oanfalh following their enthusiasm when using Sense of touch. The study in the first chapter of the research problem to reveal the role played by the process of cognition and its relationship with the touch function of the industrial product and the associated defect in performance and harder to use. The study also pointed to the research objectives and the importance of what gave him the information sings industrial designer and supports the design aspects of the relationship between global study perception stereotactic and Alozivih.fima touched second chapter to the concept of perception and its importance and how it is done through the delivery of perceptions to the brain, to be responsive and accessible then to the process stages Aladrakih.ouchml final chapter findings and recommendations and proposals have been the most important the following results:1-ahtot sample Find the perfect high values in terms of the functional level to come compatible with the perception stereotactic required as a target for research and 100%. 2-amtazat aesthetic value of the research sample appeared manifested in color and texture to come compatible with the public taste for users to Ha.bnsph 100%3-ba models Search and crossed markedly from which the desired functional value and the extent of consistency with the level of perception stereotactic according to private employment considerations and by 80%